Distribution of sea cucumbers, Holothuria atra, on reefs in the upper Gulf of Thailand and the effect of their population densities on sediment microalgal productivity. (5th April 2020) - Viyakarn, Voranop; Chavanich, Suchana; Heery, Eliza; Raksasab, Chalothon
Abstract: Populations of sea cucumbers in Thailand have been declining because of overfishing in recent years; however, little is known about the possible long-term effects of this decline on the sea cucumber population and reef communities. The purpose of this study was to examine the distribution patterns and habitat compositions of Holothuria atra in the upper Gulf of Thailand. In addition, field and laboratory experiments were conducted to investigate the impact of sea cucumber density and feeding activity on the sedimentary microalgal community. The results showed that there was a correlation between the density of H. atra and substrate composition. The density of H. atra increased as the percentage of sand cover in the habitats increased. High concentrations of chlorophyll– a were detected in gut contents. In addition, results from field and laboratory experiments showed that when H. atra was absent, a high concentration of chlorophyll- a in the reef sediment was recorded. The higher the number of H. atra, the greater the capability to reduce the microalgal biomass in the sediment. Thus, H. atra plays an important role in recycling nutrient in reefs in the Gulf of Thailand, and consequently, a decline in the sea cucumber population may alter the reef community. Highlights: There is a world-wide serious issue on overharvesting of sea cucumber populations. This is the first study in Thailand to investigate the effect of decline and increase of sea cucumber populations on sediment reef ecosystem. The decrease and increase of sea cucumbers had significantly affected on benthic microalgal production in sediments.